2000
DOI: 10.1021/es990376g
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of SeO42- Anions and Anoxic Formation of Iron(II)−Iron(III) Hydroxy-Selenate Green Rust

Abstract: Iron(II)-iron(III) hydroxy-salts known as green rusts were recently discovered as minerals present in hydromorphic soils and sediments. Due to their high reactivity, they are envisioned as potential reducing agents of a number of pollutants such as nitrate, chromate, or selenate. The interaction of selenate ions with such iron(II)-containing hydroxy compounds was studied by monitoring the oxidation processes of the iron phases with transmission Mo ¨ssbauer spectroscopy measured at 14 K and by following the evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(73 citation statements)
references
References 29 publications
4
67
0
2
Order By: Relevance
“…In contrast studies concerning the other type of stacking for GR, i.e. GR2 as obtained for SO 4 2j or SeO 4 2j , led to one unique value of x at 0.33 [2,8].…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast studies concerning the other type of stacking for GR, i.e. GR2 as obtained for SO 4 2j or SeO 4 2j , led to one unique value of x at 0.33 [2,8].…”
Section: Methodsmentioning
confidence: 85%
“…Hydroxychloride GR1(Cl j ) was prepared this way by adjusting the excess of Cl j with respect to the stoichiometry of Fe(OH) 2 when mixing FeCl 2 and NaOH. A large range of composition was obtained from {[Cl j ]/[OH j ]} = 1.14 to 1.20, which led to compounds Fe II 3 Fe III (OH) 8 Cl [3] and Fe II 2 Fe III (OH) 6 Cl [4], respectively. XRD patterns were those of a GR1 with parameters a 0 = 0.319 nm and c = 2.385 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The data also indicate that microbial populations are very important in this transformation as demonstrated in comparing the iron amendment column results. There have been reports of green rust independently reducing selenate [42,51]. If this were the only factor in reduction and binding of the Se, then the extracted Se would be consistent in all of the columns containing iron.…”
Section: Flow-through Column Experimentsmentioning
confidence: 95%
“…Thus, the differences in Cr(VI) removal in these experiments suggests an additional reduction mechanism, namely heterogeneous reduction of Cr(VI) by secondary Fe(II) precipitates such as Fe(OH) 2 or green rust. Refait et al (2000) found green rust formation through reduction of Se(VI) by Fe(OH) 2 as indicated by the reaction: …”
Section: Chromate Reduction By Preaged Biotite In Naoh Solutionsmentioning
confidence: 99%